Chiral Hydroxamic Acid Ligands in Asymmetric Synthesis: The Evolution of Metal‐Catalyzed Oxidation Reactions. Issue 11 (14th March 2023) - Janardan Pawar, Tushar; Bonilla‐Landa, Israel; Reyes‐Luna, Alfonso; Barrera‐Méndez., Felipe; Javier Enríquez‐Medrano, Francisco; Enrique Díaz‐de‐León‐Gómez, Ramón; Luis Olivares‐Romero, José
Abstract: Asymmetric oxidation reaction is one of the significant pathways in stereoselective reactions, which is a prominent performer in academic and industrial research. However, ligands are vital for planning an ideal metal‐catalyzed asymmetric oxidation reaction as they interact with the metal to construct catalytically active metal complexes, which can catalyze numerous asymmetric reactions. Designing and synthesizing novel chiral ligands is essential for researchers in modern asymmetric synthesis. In this course, exploring the applicability and the survey of hydroxamic acid as a vital ligand has been presented, which is essential for various metal‐catalyzed transformations. Abstract : In asymmetric metal‐catalysis, bishydroxamic acid is an essential ligand for the enantioselective oxidation reactions. These ligands can allow not only oxidation reactions but also epoxidation, dearomatization, ring‐closing, ring opening, 1, 3‐dipolar cycloaddition, anti‐dihydroxylation and many more. In this minireview, the development and application of this ligand are discussed.